2015
DOI: 10.5603/ep.a2017.0044
|View full text |Cite
|
Sign up to set email alerts
|

Czy istnieje różnica w jakości życia i występowaniu objawów psychiatrycznych u chorych na akromegalię i inne choroby przewlekłe?

Abstract: Psychiatric morbidity, mainly anxiety and insomnia, occurs in 50% of patients with acromegaly. However, the psychological wellbeing and mood seem to be related to other factors such as the acceptance of the illness. Thus, concerning the diagnosis, treatment, and monitoring of acromegaly an interdisciplinary approach, taking into account psychological and psychiatric consultation, is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
(36 reference statements)
1
5
0
Order By: Relevance
“…Subjects with acromegaly showed more visible physical effect including hypertension, polyarthralgia, osteoporosis, and kyphosis. Similar results were reported by Webb et al, but not Szcześniak et al, who reported worse social relationships than the general population 18,22,23…”
Section: Discussionsupporting
confidence: 90%
“…Subjects with acromegaly showed more visible physical effect including hypertension, polyarthralgia, osteoporosis, and kyphosis. Similar results were reported by Webb et al, but not Szcześniak et al, who reported worse social relationships than the general population 18,22,23…”
Section: Discussionsupporting
confidence: 90%
“…However, it should be emphasized that the relationship between the level of acceptance of the disease and the QoL domains seemed to be more significant in the controlled acromegaly subgroup where the size effect of the correlations was much bigger. The importance of perception of the illness and emotional representation of symptoms that could result in the level of acceptance affects self-perceived QoL (24,26) thus should not be ignored by health providers, rather treated as a starting point of conversation. However, biochemical normalization cannot be simply translated as lessening acromegaly burden of concomitant diseases, thus biochemical control does not equal clinical control which is more complex and multidimensional.…”
Section: Discussionmentioning
confidence: 99%
“…Intercorrelation between acromegaly, presence of depressive symptoms and satisfaction of patients was also found by Kepicoglu et al (16). This being said, psychopathology is suggested not only to be an independent factor modifying QoL (15,26,27), but also superior to biochemical control and other factors. Proper consideration of the role of psychopathology plays a major role in holistic attitude toward such patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acromegaly worsens both the physical and emotional well-being of patients, and substantially reduces quality of life (QoL) at all disease stages [2]. Patients with acromegaly have much lower scores on generic questionnaires measuring QoL compared to the general population or patients with other chronic diseases, such as asthma, angina, and osteoarthritis [3][4][5]. The physical aspect of QoL in acromegaly is substantially affected by pain, weakness, sleep problems, and limitations of daily activities [6].…”
Section: Introductionmentioning
confidence: 99%